2022
DOI: 10.3389/fonc.2022.875521
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Transcriptome Data Revealed AURKA and KIF20A as Critical Genes in Medulloblastoma Progression

Abstract: Medulloblastoma is the neuroepithelial tumor with the highest degree of malignancy in the central nervous system, accounting for about 8% to 10% of children’s brain tumors. It has a high degree of malignancy and is easily transmitted through cerebrospinal fluid, with a relatively poor prognosis. Although medulloblastoma has been widely studied and treated, its molecular mechanism remains unclear. To determine which gene plays a crucial role in medulloblastoma development and progression, we analyzed three micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Moreover, expression profiling of pediatric brain tumors has shown that AURKA was consistently and highly overexpressed (up to 106-fold) in tumor samples from all glioma grades and from patients varying from 4 months to 82 years old; however, mRNA expression showed only weak correlation with the Ki-67 labeling index, and significant associations with poor patient survival were only observed for GBM [ 530 ]. Overexpression of AURKA is also linked with survival in MB patients [ 531 ].…”
Section: Protein Kinases In Pediatric Oncology and Their Association ...mentioning
confidence: 99%
“…Moreover, expression profiling of pediatric brain tumors has shown that AURKA was consistently and highly overexpressed (up to 106-fold) in tumor samples from all glioma grades and from patients varying from 4 months to 82 years old; however, mRNA expression showed only weak correlation with the Ki-67 labeling index, and significant associations with poor patient survival were only observed for GBM [ 530 ]. Overexpression of AURKA is also linked with survival in MB patients [ 531 ].…”
Section: Protein Kinases In Pediatric Oncology and Their Association ...mentioning
confidence: 99%
“…Animals were kept in the infrastructure of the Laboratory Animal Services Center (LASC), University of Zurich. 10…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…AURKA controls centrosome maturation, bipolar spindle assembly, and cytokinesis, while AURKB and AURKC allow chromosome condensation, attachment to kinetochores and their alignment during metaphase and cytokinesis 9 . AURKA was identified as critical gene involved in MB progression 10 and AURKA inhibition in MB cell lines was found to increase chemosensitivity 11 . Exposure of SHH MB models to pan-AURK inhibitors were reported to enhance the sensitivity to conventional chemotherapies in vitro and in vivo 12 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 , 12 ] KIF20A is involved in regulation of microtubule bundle formation, midbody separation and cytokinesis. [ 13 ] Pathways associated with KIF20A include cell cycle, mitosis, and responses to cytosolic Ca2 + elevation. [ 14 ] Gene ontology (GO) annotations linked to KIF20A included protein kinase binding and ATP hydrolysis activities.…”
Section: Introductionmentioning
confidence: 99%